PRAKTIK PENEBANGAN POHON DI HUTAN LINDUNG DALAM PELAKSANAAN PACU JALUR DIKAITKAN DENGAN UNDANG-UNDANG NOMOR 18 TAHUN 2013 TENTANG PENCEGAHAN DAN PEMBERANTASAN PERUSAKAN HUTAN - RONALDO GUSTI SANDRA; Erdianto Effendi; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Halal tourism is a tourist visit activity with tourism destinations and industries that prepare product, service and tourism management facilities that meet the elements of sharia. With this Islamic tourism, the world community is introduced to the nobility and greatness of Islamic culture. Therefore, this thesis discusses how the juridical analysis of Regional Regulation Number 2 of 2017 concerning Halal Tourism in Siak Regency? and what is the ideal arrangement regarding Halal Tourism in Siak Regency?.This type of research can be classified in the type of normative legal research. In this normative legal research, the author is interested in conducting research using the criteria of legal history and legal comparisons. Sources of data used, namely: secondary data in the form of primary legal materials, secundr legal materials and tertiary legal materials. The data collection technique in this research is literature review. Data analysis was carried out qualitatively, namely the data obtained did not use statistics or mathematics or the like.The conclusions of this study are firstly, Regional Regulation Number 2 of 2017 concerning Halal Tourism in Siak Regency has shortcomings and weaknesses because it does not include content material regarding sanctions so that it affects its implementation and causes Regional Regulation Number 2 of 2017 concerning Halal Tourism in Siak Regency not yet. effectively implemented as it should. Meanwhile, the purpose of the sanctions is to regulate community non-compliance, so that people obey the applicable law. Second, regulations regarding halal tourism must be in accordance with sharia principles in terms of legal regulations and their application. Alignment of legal rules accompanied by implementation in accordance with the provisions is a way of realizing halal tourism that is based on sharia principles and is carried out with sharia principles. Therefore it is necessary to include strict sanctions in Regional Regulation Number 2 of 2017 concerning Halal Tourism in Siak Regency, so that the ideal regulations related to the implementation of Halal Tourism in Siak Regency are realized. The author's advice, namely to the government as the maker of laws and regulations to revise Regional Regulation Number 2 of 2017 concerning Halal Tourism in Siak Regency, which includes strict sanctions so that ideal regulations are realized related to the implementation of Halal Tourism in Siak Regency.Keywords: Halal Tourism - Regional Regulations - Siak Regency.